Entrepreneurial Saving Practices and Reinvestment: Theory and Evidence. Issue 4 (10th January 2017) - Beck, Thorsten; Pamuk, Haki; Uras, Burak R.
Abstract: We use a novel enterprise survey to gauge the relationship between saving instruments and entrepreneurial reinvestment. We show that while most informal saving practices are not associated with a lower likelihood of reinvestment when compared with formal saving practices, there is a significantly lower association of saving within the household with the likelihood of reinvesting profits than other savings form, most importantly, formal saving forms. This result is robust to the model specification and controlling for a large array of variables including district‐level fixed effects. We also provide empirical tests to address reverse causation and omitted variable concerns. Our work contributes to the debate on the implications of different saving instruments in developing countries and expands the entrepreneurial financing constraints literature by focusing on internal rather than external funding constraints.